2009
DOI: 10.1111/j.1467-7687.2009.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of verbal abilities in children and adolescents

Abstract: The etiology of individual differences in general verbal ability, verbal learning and letter and category fluency were examined in two independent samples of 9-and 18-year-old twin pairs and their siblings. In both age groups, we observed strong familial resemblance for general verbal ability and moderate familial resemblance for verbal learning, letter and category fluency. All familial resemblance was explained by genetic factors. There was significant covariance among the tests, which was stronger in magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
9
0
4
Order By: Relevance
“…Across this 8‐year age range spanning early to middle childhood, the authors found considerable stability in genetic influences (cross‐age r g = 0.57) but also significant change (Davis, Haworth & Plomin, 2009). A second recent twin study of cognitive development employed two complementary twin cohorts who were assessed at different ages on verbal abilities (Hoekstra, Bartels, van Leeuwen & Boomsma, 2009). They showed that verbal abilities have a similar genetic architecture in childhood (9‐year‐olds) and late adolescence (18‐year‐olds), that is, the degree of genetic overlap between different subdomains of verbal ability was similar across the two ages.…”
Section: Developmental Quantitative Geneticsmentioning
confidence: 99%
“…Across this 8‐year age range spanning early to middle childhood, the authors found considerable stability in genetic influences (cross‐age r g = 0.57) but also significant change (Davis, Haworth & Plomin, 2009). A second recent twin study of cognitive development employed two complementary twin cohorts who were assessed at different ages on verbal abilities (Hoekstra, Bartels, van Leeuwen & Boomsma, 2009). They showed that verbal abilities have a similar genetic architecture in childhood (9‐year‐olds) and late adolescence (18‐year‐olds), that is, the degree of genetic overlap between different subdomains of verbal ability was similar across the two ages.…”
Section: Developmental Quantitative Geneticsmentioning
confidence: 99%
“…Both the early studies reviewed by Stromswold (2001) and later studies (e.g. Hayiou-Thomas, Kovas, Harlaar, Plomin, Bishop & Dale, 2006;Hoekstra, Bartels & Boomsma, 2009) have found significant heritability for language, and some evidence for increasing heritability with age. For example, Hoekstra et al (2007) found .48 heritability for language at age 5 and .84 at age 18.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, the heritability of task performance was not detected. Previous studies have demonstrated that executive functions, including verbal fluency, were highly heritable (Friedman et al., ; Hoekstra, Bartels, van Leeuwen, & Boomsma, ; Polderman et al., ). Heritability was also indicated for task performance in the aforementioned adult twin NIRS study (Sakakibara et al., ).…”
Section: Discussionmentioning
confidence: 98%